Impulsive Purchase Behaviour of Muslim Women on TikTok Shop: Findings from West Java - Nugraha, Yudha Dwi; Permana, Rezi Muhamad Taufik; ., Azib; Hadiarti, Deno (KnE Social Sciences, 2023)
This study employs the S-O-R Framework to investigate the factors influencing browsing and impulsive consumption of cosmetic products among Muslim women on TikTok Shop. The primary focus of this investigation is to understand impulsive buying behavior among Muslim women customers in Indonesia. The findings of this research offer valuable insights to companies and cosmetic brands seeking to enhance their marketing strategies for stimulating impulsive behavior among Muslim women customers on TikTok Shop. To gather data, an online survey was conducted, involving 100 Muslim women consumers. Covariance-based structural equation modeling was utilized to assess two hypotheses. The results indicate that store promotion has a positive and significant relationship with hedonic browsing. Additionally, hedonic browsing was found to have a positive and significant effect on impulse purchase behavior. The implications of these findings for managers and scholars are further discussed. Keywords: store promotion, hedonic browsing, impulse purchase behavior